Derivatizações aniônica e catiônica de resíduos do processamento dos fios de algodão para remoção de corantes têxteis - Baldo, Gizele Rejane (2014)
The Brazilian textile industry occupies an important role in the economy and ranks among the 10 largest world producers The effluents generated in the process of fabrics dyeing contain 15 to 50% of dyes and others contaminants. With a view to environmental remediation of these effluents, the processing of cotton yarn waste (cotton dust waste - CDW) that is collected in the plant itself, proved to be an attractive material for the removal of the residual dyes effluents after the chemical derivatization with monochloroacetic acid (MCAA) or diethylaminoethyl chloride.hydrochloride (DEAE+reagent), thus originating matrices carboxymethyl- CDW (CM--CDW) and diethylaminoethyl-CDW (DEAE+-CDW), respectively. These matrices were obtained using experimental designs, when for CM--CDW three factors were evaluated: a) concentration of NaOH; b) volume of isopropanol and c) amount of MCAA, while for DEAE+-CDW, the factors were: a) concentration of NaOH and b) amount of DEAE+reagent. These matrices were tested for their effectiveness in the retention of dyes: the cationic, C. I. Basic Blue 41 (BB 41) and the anionic, C. I. Reactive Red 239 (RR 239), both in column and batch experiments. Also, the biodegradability of these materials was tested. For the best matrices obtained, additional experiments regarding the retention efficiency of the dyes (initial concentration, contact time and addition of salts) and matrices biodegradability after the dye retention were also carried out. For the CM--CDW, the efficiency of uptake of the cationic dye was predominantly determined by the concentration of alkali. The inclusion of the higher volume of isopropanol in the pretreatment step resulted in improved efficiency, but with an additional cost not justifiable. The best matrix obtained in the absence of isopropanol showed retention values for column and batch experiments with respective efficiencies of 3.9 and 2 times higher than a commercial CM-cellulose. For the biodegradability test, the samples of experimental design showed close enzymatic hydrolysis compared with the controls with alkali. For the DEAE+-CDW, the main variable for the efficiency of dye retention is predominantly determined by the amount of DEAE+reagent. The maximum retention of the anionic dye was obtained in columns while the batch alternatve performance was close to that of a commercial DEAE-Cellulose. The biodegradability test revealed that the derivatization with DEAE+reagent reduced the percentage of hydrolysis by cellulases when compared to the controls with NaOH. The initial concentration test of dye indicated that the retention increases with increased dye concentration and contact time to reach equilibrium which was higher in the higher concentrations in both matrices. The addition of NaCl decreased the dye retention for the carboxymethylated matrix and for the diethylaminoethylizated matrix the influence was positive only after addition of 50 mM. The presence of dye in the matrices derivatized reduced the hydrolysis in 4.10 and 37.36 % for carboxymethylated and diethylaminoethylizated matrices, respectively. Therefore, the CM--CDW and DEAE+- CDW derivatives of CDW proved effective for the removal of the dyes BB 41 and RR 239, respectively, and thus both represent important alternatives in the treatment of colored textile effluents.